Fiscal and current account imbalances: The cases of Germany and Portugal - António Afonso; José Carlos Coelho (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2021)
We investigate the bilateral relationship between government budget balances and current account balances for Portugal and Germany. We find that the response of the current account balance to the budget balance is greater in Portugal than in Germany. On the other hand, the response of the budget balance to the current balance is higher in Germany than in Portugal. In Portugal and Germany, a fiscal rules index has a negative impact on the current account balance and the government effectiveness index has a positive impact on the government balance. The public debt as a percentage of GDP positively affects the current account balance in Portugal, and in Germany it does not. During the period of implementation of the external assistance programme in Portugal, the current account balance improved, while the government balance did not.
Keywords: F32; F41; H62; C31; C32; 330; budget deficit; external deficit; Portugal; Germany; fiscal rules; time-series